Pregnancy in juvenile idiopathic arthritis: maternal and foetal outcome, and impact on disease activity. (March 2022) - Gerosa, Maria; Chighizola, Cecilia Beatrice; Pregnolato, Francesca; Pontikaki, Irene; Luppino, Angela Flavia; Argolini, Lorenza Maria; Trespidi, Laura; Ossola, Manuela Wally; Ferrazzi, Enrico M.; Caporali, Roberto; Cimaz, Rolando
Objective: This retrospective cohort study describes the modulation of disease activity during gestation and in the year following delivery as well as maternal and neonatal outcomes in a monocentric cohort of women with juvenile idiopathic arthritis (JIA). Methods: Disease activity was assessed using DAS28-CRP before conception and every 3 months during pregnancy and in the first year postpartum. The risk of complicated pregnancies was measured applying a generalized estimating equation model. Changes in disease activity during gestation and in the first year postpartum were assessed in a linear mixed model for repeated measures. Results: Thirty-one women (49 pregnancies) with persisting JIA and at least one conception were enrolled. Adjusted DAS28-CRP levels remained stable from preconception through the first trimester, but increased significantly in the second and decreased not significantly in the third. In the postpartum, adjusted disease activity peaked at 3 months after delivery, stabilized at 6 months to decrease at 1 year, although not significantly. Preconceptional DAS28-CRP and number of biological drugs predicted disease activity fluctuation during gestation. The number of biological drugs and the length of gestational exposure to biologics significantly predicted pregnancy morbidity. In particular, JIA women had a higher probability of preterm delivery compared with healthy and disease controls. Adjusted for breastfeeding and DAS28-CRP score in the third trimester, postconceptional exposure to biologics was inversely related with disease activity in the postpartum: the longer the patient continued treatment, the lower the probability of experiencing an adverse pregnancy outcome. Conclusion: These data offer novel insights on how treatment affects disease activity during pregnancy and postpartum as well as obstetric outcomes in women with JIA.